2002
DOI: 10.1016/s0378-1097(02)00707-3
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of spread by Mycobacterium tuberculosis bacilli in A549 epithelial cell monolayers

Abstract: We developed an in vitro tissue-culture model to analyze the process involved in mycobacterial spread through lung epithelial cell monolayers. A549 cells were infected with low numbers of viable Mycobacterium tuberculosis bacilli expressing the gfp gene. Subsequent addition of a soft agarose overlay prevented the dispersal of the bacilli from the initial points of attachment. By fluorescence microscopy the bacteria were observed to infect and grow within the primary target cells; this was followed by lysis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
20
0
2

Year Published

2003
2003
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 16 publications
(21 reference statements)
0
20
0
2
Order By: Relevance
“…Apart from cell death-mediated mechanisms (see "Apoptosis as a Nonlytic Exit Strategy" and "Unconcerted Egress from the Vacuole and the Host Cell"), there is evidence for an alternative strategy of intercellular spreading for cytosolic M. marinum and M. tuberculosis in epithelial cell layers (27,32) as well as in amoebae (69). RD1, the major virulence locus of pathogenic mycobacteria that is absent in attenuated strain M. bovis BCG, has been implicated in cell lysis, egress, and dissemination (42,75,82,152).…”
Section: Ejection At the Plasma Membranementioning
confidence: 99%
“…Apart from cell death-mediated mechanisms (see "Apoptosis as a Nonlytic Exit Strategy" and "Unconcerted Egress from the Vacuole and the Host Cell"), there is evidence for an alternative strategy of intercellular spreading for cytosolic M. marinum and M. tuberculosis in epithelial cell layers (27,32) as well as in amoebae (69). RD1, the major virulence locus of pathogenic mycobacteria that is absent in attenuated strain M. bovis BCG, has been implicated in cell lysis, egress, and dissemination (42,75,82,152).…”
Section: Ejection At the Plasma Membranementioning
confidence: 99%
“…In addition, in vitro tissue culture model studies combined with fluorescence techniques have directly observed the binding and invasion of alveolar epithelial cells by M. tuberculosis (5,6). A dramatic reduction in the number of M. tuberculosis cells adhering to the extracellular matrix (ECM) 2 after preincubation of bacteria with fibronectin (Fn) was also reported (7).…”
mentioning
confidence: 99%
“…We do not know the significance of this high mBD production at the beginning of the infection; however, considering that the usual human infecting dose is very low and that bacteria can be endocytosed by epithelial cells [14], in which they induce the production of b-defensins that efficiently kill bacteria, it is plausible to propose that b-defensins could participate in the early elimination of bacilli. This bactericidal activity might be more efficient in persons who apparently do not have infection and could also participate in the establishment of latent infection.…”
mentioning
confidence: 99%